Serum Lactate Dehydrogenase Level in Acute Leukemias - Hussain, Mutaz Fawzi; Alwan, Alaa Fadhil; Fahad, Hazim Ismaeel; Saeed, Sameer Rasoul (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Acute leukemias are clonal neoplastic proliferations of immature cells of the hemopoietic system. They are divided into acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL) and acute undifferentiated leukemia (AUL). LDH has been suggested as a possible non-specific tumor marker for many years, and total serum LDH is frequently elevated in neoplastic diseases. The aims of the study are to evaluate the significance of increased serum LDH levels in patients with acute leukemia and to determine the importance of serum LDH level in the follow up and assessment of treatment responses. Patients, Materials and Methods: This study was conducted at Baghdad Teaching Hospital in Medical City during the period of October 2003 till October 2004. It included 108 patients with acute leukemias. The patient groups were compared with 21 apparently healthy control subjects. All patients had full medical history, complete physical examination, and routine investigations and other specific investigations e.g. BM aspiration and biopsy. Serum lactate dehydrogenase LDH level was estimated in all patients serially during diagnosis and after chemotherapy as well as in control subjects. Results: Total serum LDH levels were significantly higher among patients with acute leukemias compared to that of the controls. Comparing the three types of leukemic patients, no significant difference was observed in total serum LDH levels between AML, ALL and AUL patients. Regarding treatment, levels of total serum LDH were significantly decreased in both remitter and non-remitter patients with acute leukemia with no significant difference between them. Conclusion: Although total serum LDH is higher in all acute leukemic patients, it is hardly discriminator between subsets of acute leukemia and is of little value in the prognosis and prediction of treatment response and outcome.